Implementation of Positive Culture in Promoting Student Achievement and Learning Motivation: A Case Study at SD Negeri 3 Dewantara, North Aceh District) - Hasanun Hasanun; Yulia Santi; Muhammad Iqbal (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to evaluate the implementation of learning strategies and evaluation instruments focusing on content differentiation to enhance student understanding at the elementary school level. The research methodology employs a qualitative approach with multiple instrument data collection techniques. The results show that in the aspect of content differentiation, the use of Concrete Media (such as cliff boards) is the most effective strategy with a frequency of 16 references (35%), as it is able to facilitate real visualization of concepts for students. The data collection process is dominated by Observation techniques (32 references) and Grouping (29 references), indicating that direct behavioral monitoring and group dynamics are the main pillars in assessing the learning process. From the learning outcomes evaluation perspective, Oral Presentation (9 references) and Adaptive Rubric (8 references) are the most frequently used instruments for students to demonstrate their understanding. Overall, this study concludes that the combination of concrete media with structured observation methods and oral-based evaluation can significantly support the achievement of competencies and learning flexibility for elementary school students.